Experience of nurse practitioners performing colonoscopy after endoscopic training in more than 1,000 patients - Riegert, Monica; Nandwani, Monica; Thul, Bonny; Chiu, Angela Chang; Mathews, Simon C.; Khashab, Mouen A.; Kalloo, Anthony Nicholas (Endoscopy International Open, 2020)
Background and study aims The demand for screening colonoscopy has continued to rise over the past two decades. As a result, the current workforce of gastroenterologists is unable to meet the needs for colorectal cancer (CRC) screening. Therefore, solutions are needed to improve this disparity, with non-physician endoscopists being a potential option. However, current literature on the performance of non-physicians in endoscopy is limited. The aim of this study was to assess the quality of colonoscopy performed by three gastrointestinal fellowship-trained nurse practitioners (NPs).Methods This was a retrospective study performed at a single tertiary academic medical center. Colonoscopies performed by three gastrointestinal-specialized NPs after having completed training of at least 140 supervised colonoscopies were reviewed for analysis. Inclusion criteria were patients undergoing colonoscopy for colorectal cancer screening purposes. Outcomes included colonoscopy quality indicators as defined by the American Society for Gastrointestinal Endoscopy/American College of Gastroenterology Taskforce (ASGE/ACG) Taskforce.Results The study included 1,012 subjects (mean age 56.2 years, female 51.5 %, African American 73.9 %) who underwent screening colonoscopies by three NPs. Cecal intubation was successful in 997 subjects (98.5 %). Mean adenoma detection rate was 35.6 %. Mean withdrawal time was 18.9 minutes. There were no adverse events including colonic perforations or delayed post-polypectomy bleeding.Conclusions Three fellowship-trained NPs in colonoscopy in the United States satisfied the quality indicators proposed by the ASGE/ACG Task force, demonstrating that adequately trained NPs can perform colonoscopy safely and effectively. With the demand for colonoscopy exceeding the supply, non-physicians could be part of the solution to meet the demands for CRC screening.